2019
DOI: 10.3389/fchem.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Renewable Epoxy-Amine Resins With Tunable Thermo-Mechanical Properties, Wettability and Degradation Abilities From Lignocellulose- and Plant Oils-Derived Components

Abstract: One-hundred percent renewable triphenol—GTF—(glycerol trihydroferulate) and novel bisphenols—GDF x –(glycerol dihydroferulate) were prepared from lignocellulose-derived ferulic acid and vegetal oil components (fatty acids and glycerol) using highly selective lipase-catalyzed transesterifications. Estrogenic activity tests revealed no endocrine disruption for GDF x bisphenols. Triethyl-benzyl-ammonium chloride (TEBAC) mediated glycidylation of all bis/triphenols, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…A sustainable approach to solve this plastic waste problem to some extent is designing and using renewably sourced and biodegradable polymers. [235] Examples are the synthesis of biobased acrylic polymers using 2H-HBO derived from renewable sources [236] or from bio-based Cyrene TM , [237] bio-based watersoluble aromatic polymers produced from lignin-based compounds, [238] bis-phenols, and trisphenol from renewable resources for the production of poly(ester urethane)s, and epoxy-amine resins, [239][240][241][242][243] to name a few. Edible films have also entered the packaging market as a sustainable solution to plastic waste.…”
Section: Other Challengesmentioning
confidence: 99%
“…A sustainable approach to solve this plastic waste problem to some extent is designing and using renewably sourced and biodegradable polymers. [235] Examples are the synthesis of biobased acrylic polymers using 2H-HBO derived from renewable sources [236] or from bio-based Cyrene TM , [237] bio-based watersoluble aromatic polymers produced from lignin-based compounds, [238] bis-phenols, and trisphenol from renewable resources for the production of poly(ester urethane)s, and epoxy-amine resins, [239][240][241][242][243] to name a few. Edible films have also entered the packaging market as a sustainable solution to plastic waste.…”
Section: Other Challengesmentioning
confidence: 99%
“…Although many studies have focused on utilizing lignin in epoxy resin, [23,27,33,34] they mostly used modified lignin (fractionated or lignin monomers) [23,27,29] . For instance, several studies used small compounds obtained from lignin, including syringaresinol, [35] isosorbide diferulate, [36,37] bisguaiacol, [22] diphenolic acid, [38] and ferulic acid [39–41] to synthesize epoxy resins. They reported that the cured epoxy thermosets made with lignin‐derived monomers/dimers had comparable properties to DGEBA thermosets, and properties of the epoxy systems can be tunable by using various curing agents.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of water subjected to surface defects, the angle of touch with air is 180°or higher (Yuan and Lee, 2013). The scanning electron microscopy machine can be used to examine the distribution and obvious adhesion of particles together with the polymer matrix (dos Santos Barros et al, 2019;Luz et al, 2008;Hu et al, 2020;Hollande et al, 2019). The good wettability of the composites demonstrates well-spreading particle distribution, as well as the appearance of microbubbles and agglomerates.…”
Section: Wettabilitymentioning
confidence: 99%